2003
DOI: 10.1002/cb.116
|View full text |Cite
|
Sign up to set email alerts
|

Use it or lose it: purchase acceleration effects of time‐limited promotions

Abstract: While researchers have examined the impact of retail promotions on purchase acceleration in the past, the distinction between time‐limited and time‐independent promotions has not been made in this context. In this paper, the authors report findings from two studies. In Study 1, it was found that promotions of short duration (time‐limited), such as store coupons, accelerate purchases, whereas promotions of longer duration (time‐independent), such as manufacturer's coupons, have no such impact. In Study 2, the i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
59
0
1

Year Published

2005
2005
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 107 publications
(62 citation statements)
references
References 16 publications
(21 reference statements)
2
59
0
1
Order By: Relevance
“…This forced urgency seems to compel consumers to decide and several authors have been thriving to find the optimal timing for promotions to have the desired impact on sales (e.g., Chiang, Lin, & Chin, 2011). Research has also revealed that consumers are sensitive to the promotion and its deadline, even when the reference price is exaggerated (Aggarwal & Vaidyanathan, 2003), and that these conditions increase their buying intentions (Krishnan, Dutta, & Jha, 2013). Therefore, in addition to understanding how experimental TP (deadline to task completion) affects decision-making, it is important to investigate how other TP types, namely stock-out threat and price-promotions, affect consumer decisions.…”
Section: Time Pressure: Alternative Manipulationsmentioning
confidence: 99%
“…This forced urgency seems to compel consumers to decide and several authors have been thriving to find the optimal timing for promotions to have the desired impact on sales (e.g., Chiang, Lin, & Chin, 2011). Research has also revealed that consumers are sensitive to the promotion and its deadline, even when the reference price is exaggerated (Aggarwal & Vaidyanathan, 2003), and that these conditions increase their buying intentions (Krishnan, Dutta, & Jha, 2013). Therefore, in addition to understanding how experimental TP (deadline to task completion) affects decision-making, it is important to investigate how other TP types, namely stock-out threat and price-promotions, affect consumer decisions.…”
Section: Time Pressure: Alternative Manipulationsmentioning
confidence: 99%
“…Our readership may not necessarily be loyal, and is unlikely to protest our media absence, but they do represent a predisposed and accessible segment through which we can grow our patronage. Secondly, the framing of restrictions -in this case, by limiting the number of tickets available and linking them to a single event -can accelerate consumer interest and redemption intentions (Krishna and Zhang, 1999;Aggarwal and Vaidyanathan, 2003). Thirdly, the actual 'VIP Entry Pass' used in the newspaper promotion did not differ at all from the others issued, in that it was valid for a full three months; however, none was redeemed except at the meeting with which the article was linked.…”
Section: Resultsmentioning
confidence: 99%
“…A price discount is a temporary action that affects consumers' motivation to process information relative to a brand and increases the incentive of a possible purchase in the short term (Alba, Mela, Shimp, & Urbany, 1999;Grewal, Marmorstein, & Sharma, 1996). It generates a time constraint effect that affects consumer purchase behaviour (Aggarwal & Vaidyanathan, 2003). As previously discussed, depending on the type of promotional activities and the target markets, the increase of sales volume may stem from different sources including: the purchase of larger quantities by current buyers of the brand, the attraction of new buyers in the product category who previously did not buy either brand, or the attraction of consumers who usually buy the competitor's brand (Ailawadi, 2001).…”
Section: The Modelmentioning
confidence: 99%